Organizational Justice and Organizational Commitment in workers of the mining sector in Peru - Ríos Díaz, José Y. (2019)
The objective of this research was the relationship between the variables of organizational justice and organizational commitment in a sample of 53 workers from the mining sector of Peru, as well as the administration of the Organizational Justice Scale and the Organizational Commitment Questionnaire. The hypothesis that was raised was the association between organizational justice and organizational commitment; Likewise, some hypotheses related to the dimensions of organizational justice are raised with the dimensions of organizational commitment. The findings of this exploratory study show that there is a relationship between organizational justice and organizational commitment; While an analysis between the dimensions, the interpersonal relationship and the affective commitment.